Menjaga Demokrasi di Tengah Keberagaman: Tantangan dan Strategi Politik Multikultural - Nurhidayah, Anis; Novriza Setya Dhewantoro, Happri; d Bautista, Lloyd (JURNAL TAPIS, 2025)
In the context of democracy, such diversity presents both a strength and a complex challenge. Issues such as identity politics, policy discrimination, radicalism, and the lack of political representation for minority groups threaten democratic stability if left unaddressed. This study aims to fill that gap by analyzing how education can be a transformative tool in promoting tolerance, equality, and active citizenship. Using a literature review method, this study critically examines scholarly sources on political education, democracy, and multiculturalism in Indonesia. The findings show that multicultural and democratic education play a strategic role in shaping inclusive civic values and strengthening democratic participation across diverse societal groups. This analysis contributes to current discourse by emphasizing education not merely as a pedagogical process, but as a structural mechanism in democratic consolidation within multicultural societies. Therefore, this study offers a conceptual advancement for political education scholarship and policy development in plural democracies.